Fog Computing (Trinity Journal of Management, IT & Media (TJMITM), 2017)
every day. Some of us have multiple cell phone devices,  numerous types of laptops, smart cars, and many other wireless  devices that consume the internet to transmit data from one  position to another. The need for so many devices has grown  In the present scenario, we consider a new rising technology is  known as Fog Technology where the computing takes place at  the edge of network which is the advanced version of the cloud  computing . The Internet of Things (IoT) represents an innovative  world of information and communication technologies for anyone  can get connectivity at anyplace at anytime. Fog provides the  data, storage, computation and services like the cloud. Paper  represents the overview of the Fog computing, applications of  fog computing and how it is different from cloud computing. The  Fog computing coincides with other forms of rising technology  and what impact of this technology will have on the future of  information technology.
Keywords: Internet of Things; Fog Computing; Edge Computing